Reduction of gaseous nitrogen loss from soil applied with beneficial bacteria under different levels of N - Akter, Amaily; Kee Zuan, Ali Tan; Kasim, Susilawati; Mohd Amin, Adibah; Ab Aziz, Zakry Fitri; Rahmatullah, Noor Md; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Rahman, Md Ekhlasur (Taylor and Francis Group, 2023)
Currently, there is an abundance of interest in the methods to reduce ammonia (NH3) volatilization and nitrous oxide (N2O) emissions from cultivated soils. Nitrogen use efficiency (NUE) of applied urea is decreased due to gaseous loss, which also lowers soil N (Nitrogen) content. The purpose of this study was to investigate the potential of microbial-based inoculants to decrease NH3 loss and N2O emissions under controlled conditions. Bacillus subtilis ;(UPMB10), and Bacillus tequilensis ;(UPMRB9) in combination with five different nitrogen (N) fertilizer levels 0%, 25%, 50%, 75%, and 100% were used in this study. Results showed that NH3 cumulative volatilization loss was greater in uninoculated soil treated with a full dose of fertilizer-N (507.27 mg/kg) compared with bacterial-inoculated soil (491.20 mg/kg and 500.71 mg/kg for UPMRB9 and UPMB10, respectively). Emission of N2O increased to a greater level (15.11 mg/kg for B0N100) in uninoculated soil compared to inoculated soil (14.65 mg/kg for UPMRB9N100 and 14.93 mg/kg for UPMB10N100-treated soil) and emission of N2O increases as N application increases. Initially, the emission of N2O was greater which decreased from the sixth day until it became zero. In B0N100-treated soil, emissions of N2O increased and after 30 days of incubation, the inoculated soil had a greater N concentration than the uninoculated soil. The total N loss from applied urea was higher in uninoculated soil than in inoculated soil. According to the findings, microbial inoculants have the potential to reduce the loss of N through NH3 volatilization and N2O emissions.